Prayers offered to sea god Varuna - Mumbai Archive Project Team (Jio Institute, 2024)
Prayers are offered to Darya Raja or Varuna to ensure safety on long sea voyages, which is essential for Kolis fishermen to carry out deep-sea fishing and maritime trade.